An EEG study of human trust in autonomous vehicles based on graphic theoretical analysis - Xu, Tao; Dragomir, Andrei; Liu, Xucheng; Yin, Haojun; Wan, Feng; Bezerianos, Anastasios; Wang, Hongtao (Frontiers in Neuroinformatics, 2022)
With the development of autonomous vehicle technology, human-centered transport research certainly will be shifted to the interaction between humans and vehicles. Therefore, the motivation of this study focuses on the human trust variation in autonomous vehicles as the technology becomes increasingly intelligent. This study uses electroencephalogram data to analyze human trust in autonomous vehicles during simulated driving conditions. Two driving conditions, the semi-autonomous and the autonomous, which correspond to the two highest levels of automatic driving, are used for the simulation, accompanied by various driving and car conditions. The graph theoretical analysis is the primary method for data analysis. In semi-autonomous driving mode, the local efficiency and cluster coefficient are lower in car-normal conditions than in car-malfunction conditions with the car approaching. This finding suggests that the human brain has a strong information processing ability while facing predictable potential hazards. However, when it comes to a traffic light with a car malfunctioning under the semi-autonomous driving mode, the characteristic path length is higher for the car malfunction manifesting a weak information processing ability while facing unpredictable potential hazards. Furthermore, in fully automatic driving conditions, participants cannot do anything and need low-level brain function to take emergency actions as lower local efficiency and small worldness for car malfunction. Our results can shed light on the design of the human-machine interaction and human factor engineering on the high level of an autonomous vehicle.